Agensi Perempuan Penyintas dalam Inisiatif Keadilan Transisi di Tingkat Lokal - Mulki Makmun; Atnike Nova Sigiro (Jurnal Perempuan, 2021)
This article will describe the contribution of women survivors of human rights violations in promoting transitional justice initiatives at the local or community level in Indonesia. In their marginal position, both as women and victims of human rights violations, the women survivors show their agencies to face social, political, cultural and structural barriers. The initiatives and participation of women survivors in Central Sulawesi, Aceh, and Yogyakarta Province, have contributed to the emergence of transitional justice models at the local level, such as apologies for victims, health assistance programs, scholarships, and truth-telling. These transitional justice initiatives at the local level not only fill the gap in the accountability that should be borne by the state, but they also strengthen the implementation of transitional justice mechanisms organized by the state or government, both at the local and national levels.